2020
DOI: 10.2478/jtim-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac function in patients with sickle cell disease with left ventricular global longitudinal strain

Abstract: Background and ObjectivesThe importance of myocardial dysfunction in sickle cell disease (SCD) is currently debated. It is difficult to find a reliable index of function in patients with chronic overload as in SCD. Speckle tracking echocardiography, a new mean of evaluating cardiac function, might be a useful tool in SCD. It has been applied in many fields to detect early cardiac function deterioration, and it is less load dependent compared with other function parameters. Studies in patients with SCD are rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 29 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…was retrospective, and one (Mah et al.) was experimental 15,31–43,45,47 . Most studies obtained written consent and approval through an institutional review board or ethics committee.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…was retrospective, and one (Mah et al.) was experimental 15,31–43,45,47 . Most studies obtained written consent and approval through an institutional review board or ethics committee.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies obtained written consent and approval through an institutional review board or ethics committee. Eleven studies reported that patients were in steady state at the time of myocardial strain evaluation, defined as not being in any state of crisis or experiencing an acute event, generally for a minimum of 1 month 15,32,34–37,39–42,44,47 . The remaining six studies did not indicate timing of the patients’ last crisis in relation to myocardial strain evaluation (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations